Using Athymic Nude (FOXN1n) Mice as a Model to Study the Maternal Care and Levels of Ultrasonic Vocalization - Jouda, Jamela A (Al-Nahrain Journal of Science, 2018)
The correlation between the numbers of ultrasounds produced by pups and the different measures of retrieving behavior of their mother was investigated using athymic nude mice (Foxn1n) and their heterozygous thymus-bearing littermates (Foxn1n/Foxn1+) as a models. Significantly higher latencies of retrieve Foxn1n as compared to Foxn1n/ Foxn1+ pups on 1-pnd (postnatal day) were reported, while no differences on 3-pnd were detected. Many ultrasound vocalization parameters were investigated but the more important results were: 1) While no differences in alone group (every model alone in the cages with their biological mother), significant higher latency of start calling and average call duration of Foxn1n/Foxn1+ as compared to Foxn1n in together group (both models together in the same cages) were detected. On the other hand, significant lower latency of start calling of Foxn1n pups on 2-pnd in together observed as compared to that in alone group, 2) Higher call numbers and total calling time were detected in Foxn1n/Foxn1+ as compared to Foxn1n in together and alone groups on 2-pnd, and 3) While no differences in together group, statistically significant higher medium frequency modulation and bandwidth were reported in Foxn1n/Foxn1+ as compared to Foxn1n in alone group on 2-pnd.These results suggested that the maternal retrieving and USV emission of pups may be affected by genotype. The most differences were detected on 1-, 2-pnd but not on more than 3-pnd. These findings could indicate an early communication deficit in nude mice.